LIFESTYLE AS A MEDIATOR BETWEEN ECONOMIC LITERACY, SELF-CONTROL, AND HIGH SCHOOL STUDENTS’ CONSUMPTIVE BEHAVIOR - Hidayatulloh, Farid; Lestari, Fitra Dila; Wibowo, Agus (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study investigates the influence of economic literacy and self-control on students' consumer behavior, with lifestyle serving as a mediating variable. A quantitative approach was employed using SEM-PLS, involving a sample of 243 11th-grade students from public senior high schools in Cibinong District. The findings revealed that economic literacy and self-control have a significant negative impact on consumer behavior. In addition, self-control has a negative and significant effect on lifestyle, while lifestyle has a positive and significant effect on consumer behavior. Furthermore, lifestyle was found to mediate the relationship between self-control and consumer behavior, but not between economic literacy and consumer behavior. These results highlight the important role of economic understanding and self-regulation in shaping students' consumption tendencies.